The The Influence of ROA, EPS and ROE Toward Stock Price on Before and During Covid-19 Pandemic - Rozie Meidy; Lisa Aulia Julica (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
This research aims to provide empirical evidence about the influence of return on asset, earning per share, return on equity on stock price the banking company listed on the Indonesia stock exchange. This research quantitative research, including the taking of the sample in this study using the method purposive sampling theuse 38 sample companies the bank which listed in BEI in the observation period 2018-2021. The collection of data on the research done by the method of study documentation with the collection of research data from the financial reports that have been published by object research.This study uses three hypotheses. Data analysis in this study with descriptive and multiple linear regression. The results showed that: (1) the return on asset has not influence on equity on stock price the banking company listed on the Indonesia stockexchange; (2) the earning per share has influence on equity on stock price the banking company listed on the Indonesia stockexchange and (3) the return on equity has influence on equity on stock price the banking company listed on the Indonesia stockexchange.